Chitty on contracts. - Chitty, Joseph, 1838. (London : Sweet & Maxwell, 1955)
Includes index
Vol. 1. General principles -- v. 2. Specific contracts.
First published in 1826 under title: A practical treatise on the law of contracts.
Kept up to date by supplements.
Keywords: Contracts -- Great Britain